STATE RESPONSE MECHANISM WITH THE PARTICIPATION OF INTERNATIONAL ORGANIZATIONS IN CRISIS SITUATIONS THAT THREATEN THE NATIONAL SECURITY OF UKRAINE - Bielai, S. V.; Evtushenko І. В.; Poltavskij Е. М. (Honor and Law, 2019)
The analysis of legal acts, which declare the questions of national security of Ukraine. It is established that at present there is a practical need to develop guidelines that will form the essence of the organization of interaction of the security forces of Ukraine and international organizations in response to crisis situations that threaten the national security of Ukraine. A block diagram of the organization of interaction of the security forces of Ukraine and international organizations in the performance of service and combat missions to resolve the crisis situations.